Media Sosial Dan Digitalisasi: Analisis Perkembangan Fotografi Serta Industri Kreatif Indonesia - Nadya Fitri Rahmadhani; Debby Nindya Istiandari (Indo Publishing, 2025)
The development of digital technology has transformed photography, particularly through social media. This study analyzes the role of platforms such as Instagram, TikTok, and YouTube in accelerating the evolution of photography in Indonesia as part of the creative economy. Social media provides opportunities for marketing and personal branding, but it also requires photographers to quickly adapt to changes in algorithms. While offering many opportunities for creative expression, digitalization also influences the standards of quality and aesthetics in photography. The purpose of this research is to understand how photographers utilize social media to develop their work, build branding, and address the challenges arising from digitalization. This study employs a qualitative method with a descriptive approach, collecting data through in-depth interviews, participatory observation, and documentation studies, which are then analyzed thematically to identify relevant patterns, meanings, and contexts. In conclusion, social media functions as a key driver of innovation and competitiveness in photography while enriching the national creative economy ecosystem.